2019
DOI: 10.1159/000503344
|View full text |Cite
|
Sign up to set email alerts
|

How Target Animacy Affects Manual Laterality in Hylobatidae: The First Evidence in Northern White-Cheeked Gibbons (Nomascus leucogenys)

Abstract: Our study presents the first evidence on how target animacy impacts on manual laterality in the Hylobatidae and contributes to filling the knowledge gap between monkeys and great apes in primate evolution of emotional lateralization. Eleven captive individuals of northern white-cheeked gibbons (Nomascus leucogenys) were chosen as focal subjects. There were significantly more ambipreferent individuals than left/righthanded individuals for both inanimate (χ 2 (1, n = 11) = 7.364, p = 0.007) and animate (χ 2 (1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Behavioral laterality, which is believed to be closely related to hemispheric lateralization [Levy, 1977;Rosa Salva et al, 2012], is defined as a preference to employ a preferred limb or sense organ during the process of dealing with various tasks [Ward and Hopkins, 1993;Rogers et al, 2013;Wiper, 2017]. Although it was initially thought that behavioral lateralization was unique to human beings [Porac and Coren, 1981], increasing evidence has been found that behavioral lateralization is commonly seen in both vertebrates and invertebrates [Bisazza et al, 1998;Hopkins, 2007;Frasnelli et al, 2012;Zhao et al, 2015;Rogers and Vallortigara, 2017;Zhao et al, 2019Zhao et al, , 2020. Motor laterality and perception laterality are generally known as 2 main sorts of behavioral laterality, among which the former refers to the lateral behavior related to motor function (e.g., hand and foot preference) while the latter is deemed as the lateral behavior linked to perceptual function (e.g., visual and auditory laterality) [Fitch and Braccini, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral laterality, which is believed to be closely related to hemispheric lateralization [Levy, 1977;Rosa Salva et al, 2012], is defined as a preference to employ a preferred limb or sense organ during the process of dealing with various tasks [Ward and Hopkins, 1993;Rogers et al, 2013;Wiper, 2017]. Although it was initially thought that behavioral lateralization was unique to human beings [Porac and Coren, 1981], increasing evidence has been found that behavioral lateralization is commonly seen in both vertebrates and invertebrates [Bisazza et al, 1998;Hopkins, 2007;Frasnelli et al, 2012;Zhao et al, 2015;Rogers and Vallortigara, 2017;Zhao et al, 2019Zhao et al, , 2020. Motor laterality and perception laterality are generally known as 2 main sorts of behavioral laterality, among which the former refers to the lateral behavior related to motor function (e.g., hand and foot preference) while the latter is deemed as the lateral behavior linked to perceptual function (e.g., visual and auditory laterality) [Fitch and Braccini, 2013].…”
Section: Introductionmentioning
confidence: 99%